Karakterisasi Morfoagronomi Empat Aksesi Lokal Kacang Koro Pedang Putih (Canavalia ensiformis L.) - Hidayat Al Hafizh; Elea Nur Aziza; Agus Wartapa (JURNAL VIGOR, 2026)
White jack bean (Canavalia ensiformis L.) is a promising underutilized legume with potential applications as an alternative food crop and genetic resource for crop improvement. However, information on the morpho-agronomic performance of local accessions remains limited. This study evaluated morpho-agronomic variation among four local white jack bean accessions and identified accessions with desirable traits for preliminary selection. The experiment was conducted from November 2025 to March 2026 at the Teaching Factory Garden of Politeknik Pembangunan Pertanian Yogyakarta–Magelang, Indonesia. A randomized complete block design was used, comprising four accessions, namely FBKR-1060, FBKR-1062, FBKR-1064, and FBKR-631, with six replications. Quantitative traits included leaf length, leaf width, plant height, days to flowering, days to harvest, pod length, pod width, and seed diameter. Qualitative traits comprised growth habit, leaf apex shape, leaf base shape, pod shape, and seed color. Quantitative data were subjected to analysis of variance followed by Tukey’s honestly significant difference test at the 5% significance level. Significant accession effects were observed for days to flowering, days to harvest, pod length, pod width, and seed diameter. FBKR-1060 and FBKR-631 flowered and reached harvest earlier than FBKR-1062 and FBKR-1064. FBKR-1064 and FBKR-631 produced the longest pods and largest seed diameters, while FBKR-631 had the widest pods. All accessions exhibited a determinate growth habit, pointed leaf apex, obtuse leaf base, slightly curved pods, and white seeds. These findings indicate that quantitative traits are more informative than the observed qualitative descriptors for differentiating the evaluated accessions. FBKR-631 is a promising accession for further multi-environment and yield evaluations because it combines earliness with relatively large pod and seed dimensions.Keywords: accession; Canavalia ensiformis; earliness; morpho-agronomic traits; preliminary selection